21st Century Skills-Based Learning: Optimizing Virtual Reality Media through Blended Learning - Sari, Asri Ratna (Proceedings Series on Social Sciences & Humanities, 2022)
The current educational process, cannot be separated from solutions that are continuously being implemented to realize independent learning. Understanding the characteristics of students, is the main capital to improve the learning process. Generation Z that we are facing today has characteristics that are more adaptive to technology. Therefore, we must move to adapt to their characteristics in order to realize quality learning. This study aims to describe new innovations in the teaching and learning process so that they are in accordance with the character of generation Z. There are a number of 21st century skills, which should be possessed by students belonging to generation Z, as a provision for life in the future. There are a number of efforts that can be made in the current learning period, namely the use of blended learning. The use of virtual reality-based media is one solution. Therefore, the purpose of this article is directed to examine further the relationship between the concept of virtual reality media through blended learning to improve students' 21st century skills.